Addressing the agricultural financing gap in Malaysia via Manihah Agricultural Financing Model: will Islamic banks go the extra mile? - Rahman, Nur Hasnida; Zabri, Mohd Zaidi; Ali, Mohammad Mahbubi (Emerald, 2021)
Purpose – This paper introduces the concept of manihah and develops a conceptual framework to address Malaysia’s abandoned lands and food security issues. Design/methodology/approach – This is a conceptual paper based on insights from the existing literature and secondary data on food security, abandoned lands and manihah. Based on the prevailing gaps, the study proposes a conceptual framework of the Manihah Agricultural Financing Model to address Malaysia’s abandoned land and food security issues. Findings – The proposed model can address abandoned lands and food security issues due to the new incorporation of manihah within Malaysia’s agricultural and Islamic financial industries’ milieu. Research limitations/implications – This is a conceptual paper mainly intended to spark a discussion on the potentiality of manihah. Practical implications – The paper contends that Islamic banks have a crucial role in furthering the socioeconomic development agenda under the value-based intermediation (VBI). The paper will also be an excellent introduction to Islamic bank practitioners in understanding manihah’s relevance to their daily operation. Originality/value – This paper introduces manihah as the potential solution to food security issues by utilizing abandoned lands.